Sex talks : the five conversations that will transform your love life - Marin, Vanessa; Marin, Xander (Simon Element, 2023)
Demonstrating how to actually talk about sex, a sex therapist and her husband cover the five essential conversations every couple needs to have, sharing their successful advice and tried-and-tested tools for creating an extraordinary sex life.